Highly symmetric single nickel catalysts bearing bulky bis(α‐diimine) ligand: Synthesis, characterization, and electron‐effects on copolymerization of norbornene with 1‐alkene at elevated temperarure. Issue 21 (2nd August 2016) - He, Xiaohui; Deng, Yingjiao; Han, Zhilong; Yang, Yingping; Chen, Defu
ABSTRACT: Three new three‐dimensional geometry bulky α‐diimine ligands (L ) containing electron‐donating and electron‐withdrawing groups, 9, 10‐dihydro‐9, 10‐ethanoanthracene‐11, 12‐di(Ar)imine (Ar = p ‐PhCH3, L1 ; Ar= p ‐PhCl, L2 ; Ar= p ‐PhCF3, L3 .), and their corresponding single Ni(II) catalysts, NiL2 Br2 (Ni(L1)2 Br2, Ni(L2)2 Br2, andNi(L3)2 Br2, were synthesized and the molecular structure were determined by X‐ray crystallography. AllNiL2 Br2 catalysts were tested for norbornene polymerization and copolymerization of norbornene with 1‐alkene after activation with B(C6 F5 )3 . The results that the polymerization catalytic activities for norbornene up to 10 5 gpolymer /molNi ·h even at 140 °C, shown thatNiL2 Br2 catalysts have high thermal stability. Meanwhile, catalysts with electron‐withdrawing groups could achieve higher reactivity. The obtained poly(NB‐ co ‐1‐alkene)s were confirmed to be vinyl‐addition copolymers and noncrystalline. All copolymers exhibited high 1‐alkenes insertion ratio, good thermal stability ( T d > 375 °C), high molecular weight (up to 10 5 g/mol), good solubility in common organic solvents and could be processed into films with good transparency in the visible region. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3495–3505 Abstract : Three new three‐dimensional geometry bulky bis(α‐diimine) single Ni(II) catalysts, NiL2 Br2 (Ni(L1)2 Br2, Ni(L2)2 Br2, andNi(L3)2 Br2, were synthesized, characterized, and applied to catalyze norbornene polymerization and copolymerization of norbornene with 1‐alkene at elevated temperature. The thermal stability of catalysts, polymerization conditions and the relationship between activity and ligand electronic effects have been studied.